Effect of an Educational Intervention According to the PRECEDE Model to Promote Elderly Quality of Life - Parinaz Doshmangir; Shayesteh Shirzadi; Mohamad Hossein Tagdisi; Leila Doshmangir (Journal of Education and Community Health)
Introduction: Increasing elderly population has increased attention to improve quality of life in elderly people. This paper aimed to study the effect of educational intervention based on the PRECEDE model to promote quality of life in elderly. Materials and Methods: In this experimental study, 80 elderly people were randomly divided into two intervention and control groups. Planning of educational program was performed according to the PRECEDE model. Before implementing the program, Quality of life questionnaire and a self-designed and standard questionnaire according to the PRECEDE Model were filled in both groups. Both groups were followed up one month after the intervention and previous questionnaires were filled again. Collected data was analyzed using paired T-test, independent sample T-test, one way ANOVA, Chi-square and ANCOVA by SPSS-21 software. Results: Through health promotion intervention, the mean score of quality of life increased from 76.77±13.23 to 82.87±12.25. There was a significant difference between the total score of quality of life of intervention and control groups (P=0.031). In addition, findings showed a significant difference in physical, mental, environmental and social dimensions before and after the intervention (P<0.05). Conclusion: Using the PRECEDE model could help to identify influential factors on quality of life in elderly and developing effective educational programs.